COMPARATIVE ANALYSIS OF SOMATOTYPE AND VERTICAL IMPULSE LEVELS BETWEEN SAND AND INDOOR VOLLEYBALL ATHLETES (Fiep Bulletin - online, 2020)
Abstract: Indoor and sand volleyball have similar rules and movements. The jump is one of them, being present in the execution of the main foundations of both modalities. This study aimed to analyze the influence of somatotype and soil on the development of vertical thrust of sand volleyball and indoor athletes.    The Jonhson and Nelson Vertical Jump test (1979 apud MARINS; GIANNICHI, 2003) was used on 11 indoor and 10 male volleyball athletes, linked to the Foundation. Santa Catarina of Sport.  To better characterize the sample, to compare the somatotypical profile of the sand volleyball and court athletes and to verify if there is a correlation between the somatotype and vertical thrust, the Heath and Carter somatotype test was performed (1967 apud MARINS; GIANNICHI, 2003, pp. 74-89).    No significant differences were observed regarding the vertical impulsion and lower limb power between the sand volleyball and court athletes. Correlation between the components of the somatotype and power was verified: in the block correlation between mesomorph and power; in sand correlation between endomorph and power; In both groups there was a negative correlation between the ectomorph component and power. Thus, this study suggests that training on different soils (court or sand) does not interfere with vertical impulsion, and emphasizes the importance of assessing athletes' biotype, which is an excellent tool for discovering talent and verifying that athletes are within the ideal biotype for athletes. the modality in which they participate.
Keywords: Vertical jump; Power; Somatotype; Sand volleyball; Indoor volleyball